KEBIJAKAN KERINGANAN KREDIT BAGI NASABAH LPD DESA ADAT KESIMAN PADA MASA PANDEMI COVID-19 - Pramaitha, Dewa Ayu Utari; Ariana, I Komang Agus (LPPM Univ. Ibn Khaldun Bogor, 2021)
The Covid-19 pandemic has had a huge economic, social and political impact on all countries in the world. Indonesia is one of the most affected countries, especially on the economic side. During the Covid-19 pandemic, the decline in community activities was felt. This is currently happening to one of the LPDs in Bali, namely the Kesiman Traditional Village LPD. During the Covid-19 pandemic, the Kesiman Traditional Village LPD experienced a decline in savings and deposits which resulted in decreased credit distribution and was hampered. Due to the Covid-19 pandemic, many people have experienced layoffs (Termination of Employment) and lost their income so that they cannot set aside their income for savings and cannot even pay their credit. Therefore, the banking world, including the LPD, has issued a policy in providing credit relief to its customers during the Covid-19 pandemic, one of which is the Kesiman Traditional Village LPD. The solution that can be given to problems that occur at the research location is based on a circular announcement regarding loan installment payments for debtors affected by Covid-19, the Kesiman Traditional Village LPD can (if needed) provide policies to debtor customers in the form of credit restructuring. The existence of credit restructuring is an improvement effort carried out in credit activities for debtors who have difficulty fulfilling their credit installment payment obligations. Keyword : Covid-19 pandemic, credit relief, LPD Kesiman Traditional Village